DETERMINATION OF ETHANOL EXTRACT SUNSCREEN POTENTIAL OF RAMBUTAN RIND (Nephelium lappaceum L.) - Surya Ningsi; Nur Syamsi Dhuha; UL Miftahurrahmah (Universitas Islam Negeri Alauddin Makassar, 2015)
A sunscreen research to Determine the potential of rambutan rind (Nephelium lappaceum L.) ethanol extract has been conducted. This study aims to Determine the SPF value, percent transmission of erythema (% Te), and percent transmission of pigmentation (% Tp) of rambutan rind (Nephelium lappaceum L.) ethanol extract by using UV-VIS spectrophotometer.Sunscreen potential determination of rambutan rind extract is done based on the SPF value measured at a wavelength of 290-400 nm, the calculation method% of% Te and Tp at a wavelength 292.5 to 372.5 nm at concentration 10, 20, 40, 80, and 160 ppm by using a UV-VIS spectrophotometer.The results Showed that the SPF value of the extract at concentration of 10 ppm, 20 ppm, 40 ppm, 80 ppm, and 160 ppm respectively were 1.12; 1.23; 1.56; 2,37; and 5.32.The value of% Te at concentration of 10 ppm, 20 ppm, 40 ppm, 80 ppm, and 160 ppm respectively were 77.21; 62.87; 38.86; 16.18 and 3.10. The value of% Tp at concentration of 10 ppm, 20 ppm, 40 ppm, 80 ppm, and 160 ppm respectively were 88.01; 81.62; 68.41; 49.65 and 25.16. Obtained from the values, rambutan rind extract at concentration of 80 ppm has an SPF value of 2:37 the which means it has the potential for a minimum of sunscreen protection while at a concentration of 160 ppm, it has an SPF value of 5:32 the which means it has the potential of middle sunscreen protection. Rambutan rind extract at concentration of 80 ppm has a potential to protect against UV rays in suntan category with the value of percent tranmission erythema (% Te) by 16.18 and percent transmission of pigmentation (% Tp) by 49.65. At concentration of 160 ppm, it has a potential to protect against UV rays in extra protection category with the value of percent tranmission erythema (% Te) by 36.18 and percent transmission of pigmentation (% Tp) by 25.16 roomates includes in total blocks category.